Effects of Dopamine on the Immature Neurons of the Adult Rat Piriform Cortex - Coviello, Simona; Gramuntell, Yaiza; Castillo-Gomez, Esther; Nacher, Juan (Frontiers in Neuroscience, 2020)
The layer II of the adult piriform cortex (PCX) contains a numerous population of immature neurons. Interestingly, in both mice and rats most, if not all, these cells have an embryonic origin. Moreover, recent studies from our laboratory have shown that they progressively mature into typical excitatory neurons of PCX layer II. Therefore, the adult PCX is considered a “non-canonical” neurogenic niche. These immature neurons express the polysialylated form of the neural cell adhesion molecule (PSA-NCAM), a molecule critical for different neurodevelopmental processes. Dopamine (DA) is a relevant neurotransmitter in the adult CNS, which also plays important roles in neural development and adult plasticity, including the regulation of PSA-NCAM expression. In order to evaluate the hypothetical effects of pharmacological modulation of dopaminergic neurotransmission on the differentiation of immature neurons of the adult PCX, we studied dopamine D2 receptor (D2r) expression in this region and the relationship between dopaminergic fibers and immature neurons (defined by PSA-NCAM expression). In addition, we analyzed the density of immature neurons after chronic treatments with an antagonist and an agonist of D2r: haloperidol and PPHT, respectively. Many dopaminergic fibers were observed in close apposition to PSA-NCAM expressing neurons, which also co-expressed D2r. Chronic treatment with haloperidol significantly increased the number of PSA-NCAM immunoreactive cells, while PPHT treatment decreased it. These results indicate a prominent role of dopamine, through D2r and PSA-NCAM, on the regulation of the final steps of development of immature neurons in the adult PCX.